La dactilopintura para el desarrollo de la inteligencia emocional en los niños de inicial II de la Unidad Educativa Sultana de los Andes, del cantón Cumandá, provincia de Chimborazo, periodo 2021 - Narváez Sotamba, Lady Nicolle (2022)
This work is named "DACTILOPAINTING FOR THE DEVELOPMENT OF EMOTIONAL INTELLIGENCE IN CHILDREN OF INITIAL II OF THE SULTANA DE LOS ANDES EDUCATIONAL UNIT, CUMANDÁ CANTON, CHIMBORAZO PROVINCE, PERIOD 2021". It aims to determine the finger painting in the development of emotional intelligence in children of initial II. Since emotional intelligence is a set of skills that a human being attains by birth or learns during his life, in which empathy can be developed. It consists of understanding how others feel about learning to communicate correctly and thus achieve a common goal, motivation related to the commitment to reach the goals, and how positivism is maintained in the face of adversity self-control. It is the ability to recognize the feelings that one harbor and how these can affect the actions one perform. Social skills such as good interpersonal relationships guide people to success since they can achieve more things with leadership, conflict management, cooperation, and teamwork. The results will be reflected in the boys and girls who will benefit from these resources significantly, stimulating them through finger painting to originate their thoughts symbolically. The object of study is 25 male and female students, where observation was used as a technique. And as an instrument, the observation sheet consists of ten items for data collection. The information displayed that finger painting stimulates communication, creativity, and sensitivity, increasing their concentration ability. The data obtained through graphs were analyzed and interpreted. Finally, the development of emotional intelligence in children of initial II was diagnosed. It favored self-confidence who captured their ideas dreams, motivated by painting make learning be something motivating, achieving spontaneous communication, finding solutions to minor problems that arise, and transmitting their concerns to others without much difficulty.